Changes of health-related quality of life within 6 months after stroke by clinical and sociodemographic factors - Nipaporn Butsing; Joachim G. Voss; Jesada Keandoungchun; Nalinrat Thongniran; Mary T. Quinn Griffin (Scientific Reports)
Abstract Stroke causes functional disabilities and reduces the quality of life of stroke survivors. This retrospective cohort study aimed to examine changes in health-related quality of life (HRQoL) six months after a stroke and the effect of stroke characteristics and sociodemographic factors on HRQoL. Participants completed a questionnaire that included the stroke characteristics, sociodemographic characteristics, and the 5-level European Quality of Life 5 dimensions (EQ-5D-5L) before discharge. Follow-up assessments of HRQoL were performed at one, three, and six months after discharge. Descriptive statistics and linear mixed models were used for data analyses. A total of 155 first-stroke patients were included, of which N = 152 patients completed follow-up assessments until six months. The mean EQ-5D-5L index score at discharge was 0.69 (SD 0.33). The trends of HRQoL significantly increased from discharge to three months, but there was no significant HRQoL improvement after three months. Considering stroke severity, mean HRQoL significantly improved for patients with no stroke symptoms, minor stroke, and moderate stroke (p < 0.05) but not those with severe stroke (p = 0.156). HRQoL among patients with sufficient monthly income significantly increased over six months (p < 0.05). HRQoL among patients with severe stroke and having insufficient income were poor. Supportive programs are required to improve their HRQoL.